2020
DOI: 10.1177/1473325020912831
|View full text |Cite
|
Sign up to set email alerts
|

Constructing a conceptual framework for professional identity development in international social work students: A meta-ethnographic review

Abstract: There has been a significant increase of international students in Australian social work education over the past decade. Issues around international students’ language skills, cultural capital or competence, special needs and field education experiences have been explored in social work literature. However, the literature to date has a tendency to focus on international students’ deficits, or the strategies implemented to address the identified deficits. Professional identity, a critical aspect of social work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…International students can feel pressured to fully assimilate to the dominant culture of the host country in order to succeed. Yao (2020) found that for international students, assimilation and adaptation were significant factors in the professional identity development at the personal, professional, academic and cultural levels.…”
Section: Social Work Field Education and International Studentsmentioning
confidence: 97%
See 1 more Smart Citation
“…International students can feel pressured to fully assimilate to the dominant culture of the host country in order to succeed. Yao (2020) found that for international students, assimilation and adaptation were significant factors in the professional identity development at the personal, professional, academic and cultural levels.…”
Section: Social Work Field Education and International Studentsmentioning
confidence: 97%
“…International students have also identified the need to re-learn the basics, and some felt that their cultural, ethnic or linguistic backgrounds restricted their career opportunities (Yao, 2020). This is reflected in supervisors' view, that international students often did not meet the requirements for the future employer pool, despite the extra investment of time (Ross et al, 2020;Zuchowski, Hudson, Bartlett, & Diamandi, 2014).…”
Section: Social Work Field Education and International Studentsmentioning
confidence: 99%
“…Furthermore, the process of foreign students' personal development is multidimensional and is constituted by several elements. Research has found that a range of personal, linguistic, professional, academic, cultural and social elements play a significant role in their professional identity formation and preparation for the labour market (Borisenkov et al, 2020;Yao, 2021). The authors note the importance of a well-designed overseas research experience to advance intercultural, intellectual, personal, professional and academic development (Schneider et al, 2023), and this is reinforced by work that underscores the importance of individual characteristics for foreign students' adjustment and success including independence, extracurricular activity involvement, self-efficacy, cultural empathy, maintaining relationships and open-mindedness (Chennamsetti, 2020).…”
Section: Personal Developmentmentioning
confidence: 99%